IMPROVING STUDENTS READING COMPREHENSION BY USING KNOW, WANT TO KNOW, AND LEARN (KWL) TECHNIQUE - Wulandari, Eka (VISION, 2014)
Abstract The objective of this research is to identify whether the KWL can improve students reading comprehension when used in the teaching and learning process of reading comprehension in the class. The subject of the research was the Drst grade of SMAN 3 Sragen, Central Java, in the academic year of 2011/2012. The research was conducted in two cycles: the Drst cycle consisted of three meetings, and so was the second cycle. To collect the data of students reading competence, some instruments namely: tests, questionnaire, interview, and class observation were used. To ana- lyze the quantitative data which were taken from the result of stu- dents score, the researcher applied a descriptive statictics to know their enhancement in reading. The result of the research shows that KWL technique could enhance students reading comprehension in term of raising students achievement in the case of Dnding out: (a) explicit information; (b) reference of pronouns; (c) words meaning; (d) main idea in the paragraph; and (e) implicit information in the text. It means that the KWL can improve the students comprehen- sion in comprehending English texts optimally. Keywords: KWL teaching technique, students, reading comprehen- sion